Molecular Cell Biology of Apoptosis and Necroptosis in Cancer - Dillon, Christopher P; Green, Douglas R (Advances in experimental medicine and biology, 2016)
Cell death is a major mechanism to eliminate cells in which DNA is damaged, organelles are stressed, or oncogenes are overexpressed, all events that would otherwise predispose cells to oncogenic transformation. The pathways that initiate and execute cell death are complex, genetically encoded, and subject to significant regulation. Consequently, while these pathways are often mutated in malignancy, there is considerable interest in inducing cell death in tumor cells as therapy. This chapter addresses our current understanding of molecular mechanisms contributing to two cell death pathways, apoptotic cell death and necroptosis, a regulated form of necrotic cell death. Apoptosis can be induced by a wide variety of signals, leading to protease activation that dismantles the cell. We discuss the physiological importance of each apoptosis pathway and summarize their known roles in cancer suppression and the current efforts at targeting each pathway therapeutically. The intricate mechanistic link between death receptor-mediated apoptosis and necroptosis is described, as well as the potential opportunities for utilizing necroptosis in the treatment of malignancy.